2010
DOI: 10.1371/journal.pone.0010876
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Tracking of Activation Gating in Human ERG Channels Reveals Rapid S4 Movement and Slow Pore Opening

Abstract: BackgroundhERG channels are physiologically important ion channels which mediate cardiac repolarization as a result of their unusual gating properties. These are very slow activation compared with other mammalian voltage-gated potassium channels, and extremely rapid inactivation. The mechanism of slow activation is not well understood and is investigated here using fluorescence as a direct measure of S4 movement and pore opening.Methods and FindingsTetramethylrhodamine-5-maleimide (TMRM) fluorescence at E519 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 47 publications
3
52
0
Order By: Relevance
“…Protocol for Shaker-IR-A359C-C445V Ion Currents and Voltage-clamp Fluorimetry-Oocytes were prepared as previously reported (29). Oocytes were placed in a bath chamber that was perfused with control ND96 bath solution containing (in mmol/liter), 96 NaCl, 3 KCl, 1 MgCl 2 , 2 CaCl 2 , and 5 HEPES, titrated to pH 7.4 with NaOH.…”
Section: Protocols For Shaker and Shaker-ir Ion Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protocol for Shaker-IR-A359C-C445V Ion Currents and Voltage-clamp Fluorimetry-Oocytes were prepared as previously reported (29). Oocytes were placed in a bath chamber that was perfused with control ND96 bath solution containing (in mmol/liter), 96 NaCl, 3 KCl, 1 MgCl 2 , 2 CaCl 2 , and 5 HEPES, titrated to pH 7.4 with NaOH.…”
Section: Protocols For Shaker and Shaker-ir Ion Currentsmentioning
confidence: 99%
“…After 30 min of labeling, oocytes were stored in ND96 solution in the dark until voltageclamped. Fluorimetry was performed using a Nikon TE300 inverted microscope with Epi-Fluorescence attachment and a 9124b Electron Tubes photomultiplier tube (PMT) module (Cairn Research, Kent, UK) as was described previously (EsSalah-Lamoureux et al, 29). To minimize fluorophore bleaching, a Uniblitz computer-controlled shutter (Vincent Associates, Ottawa, ON, Canada) was used, and opened shortly prior to application of voltage clamp pulses.…”
Section: Protocols For Shaker and Shaker-ir Ion Currentsmentioning
confidence: 99%
“…In all hERG constructs used in this study, the two extracellular cysteines in the S1-S2 linker, C445 and C449, were mutated to valines to avoid inadvertent labeling of these cysteines by reactive agents, and thus hERG C445V:C449V:I521 is referred to as wild-type (WT) C-less. We have previously shown that the WT C-less channel has only minor effects on channel gating (8).…”
Section: Methodsmentioning
confidence: 99%
“…Further work showed that two endogenous cysteines in the S1eS2 linker distorted the signals reported by the S4-labeled positions (Es-Salah-Lamoureux et al, 2010). Removing these endogenous cysteines enabled cleaner measure of VSD activation.…”
Section: W Zhu Et Al / Progress In Biophysics and Molecular Biologymentioning
confidence: 98%